1987
DOI: 10.1093/rheumatology/26.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biochemistry in Rheumatoid Arthritis, Seronegative Arthropathies, Osteoarthritis, Sle and Normal Subjects

Abstract: Most arthritic conditions are characterized by chronic inflammation, resulting in secondary changes in serum biochemistry. In an attempt to profile different mechanisms of inflammation which might account for the clinical diversity of rheumatic diseases, we have measured C-reactive protein (CRP), plasma viscosity, serum histidine and total serum sulphydryl in 259 patients with rheumatoid arthritis (RA), 84 with ankylosing spondylitis (AS), 76 with osteoarthritis, 69 with psoriatic arthritis, 34 with systemic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…However, the serum concentration of histidine itself is not associated with knee osteoarthritis in the current study. This is consistent with previous reports21 22 in which the concentration of histidine in both serum and synovial fluid were equivalent and within the normal range in knee osteoarthritis patients but significantly lower in rheumatoid arthritis patients. However, Lamers et al 6 suggested that osteoarthritis patients had a lower level of histidine and methylhistidine in urine.…”
Section: Discussionsupporting
confidence: 93%
“…However, the serum concentration of histidine itself is not associated with knee osteoarthritis in the current study. This is consistent with previous reports21 22 in which the concentration of histidine in both serum and synovial fluid were equivalent and within the normal range in knee osteoarthritis patients but significantly lower in rheumatoid arthritis patients. However, Lamers et al 6 suggested that osteoarthritis patients had a lower level of histidine and methylhistidine in urine.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of normal CRP concentration in the majority of SLE pa tients, regardless of disease activity, is con sistent with the observations of Honig et al [1977], Pereira Da Silva et al [ ], Becker et al [1980 and Sitton et al [1987], In con trast, CRP concentration was observed to parallel disease activity in the SLE popula tions studied by Zein et al [1979] and Mor row et al [1981]. The variety of methods used, including semiquantitative capillary precipitation, radial immunodiffusion and radioimmunoassay have made interpreta tion and comparison somewhat difficult, es pecially in regard to the usefulness of ele vated CRP as indicative of infection in SLE patients.…”
supporting
confidence: 91%
“…The fact that the correlation between S and SF TN in RA is double that in SSA (Fig. 2) may be due to the greater degree of synovial barrier breakdown in RA than in SSA [32].…”
Section: Discussionmentioning
confidence: 89%
“…As the intensity of the inflammatory process and consequently tissue destruction are associated with the relative amounts of proteinase enhancers and inhibitors in the articular cavity [18,32], the TN&I-AT and TN/c~2-MG molar ratios were calculated in the SF of RA, SSA and OA patients and correlated with serum and SF inflammatory markers. Unexpectedly, it was found that RA and SSA patients had lower TN/PIs molar ratios than did OA patients (Fig.…”
Section: Discussionmentioning
confidence: 99%